Análise de limites de Índice de Irregularidade Internacional em pistas aeroportuárias com base em simulações computacionais - Sousa, Elisa da Silva (2021)
Excessive roughness on airport runways is one of the causes of damage to aircraft structures and contributes to the occurrence of accidents and incidents during landings and takeoffs. International Roughness Index (IRI) has been adopted for the assessment of this aspect at airports, although its use has some limitations, since it does not consider speeds and physical characteristics of aircraft, and vertical deviations with long wavelengths. The IRI is consolidated in the road assessment and is based on the physical characteristics of the roughness profile, which is the main factor in determining the dynamic response of the aircraft. This research aims to evaluate a longitudinal irregularity of airport runways, from different limits of acceptability of IRI, based on aircraft dynamic response. For this purpose, six roughness runway profiles were taken off, using the APRas and ProFAA software, to obtain the parameters of IRI, Pilot Station Acceleration (PSA) and Center of Gravity Acceleration (CGA), using the models: B737, B727, B777 and DC10. The profiles were adopted under the criteria of IRI limit of 2.5 m/km, this being the Brazilian standard, and the limit of 0,4 g for PSA, using 100 m long sections. A comparison was made between the results of the software used. In the analysis of different IRI limits, nine acceptability limits were adopted, ranging from 2,0 to 4,0 m/km and determined the agreement percentages between the evaluations, based on the results of IRI and PSA, considering the thirds of runways and taxiways. The results with APRas showed that, in the first and third runway thirds, the limit of 2,2 m/km were the most adequate to the evaluation, with agreements of 86% and 74%, respectively; for the second third, this value was 2,7 m/km, with 72% agreement; and in taxiways, it was 2,5 m/km, with 77% agreement. It is concluded that the use of IRI acceptability limits for each runway third may be a more adequate alternative, in relation to the use of the single limit value for the entire runway. In this way, airport pavements can be maintained more safely for aircraft traffic and decisions regarding M&R activities can be made more rationally.